Emotional responses to difficult heritage during contemporary crisis: Visitor experiences of the “War in Pori” exhibition - Väisänen, Teemu (Spain, 2026)
This article investigates how visitors emotionally engage with difficult heritage in times of contemporary crisis. The focus is the War in Pori exhibition at the Satakunta Museum in Finland, which presented local experiences of the Second World War. The exhibition opened in February 2022, coinciding with Russia’s invasion of Ukraine, which gave the historical themes of wartime disruption and resilience new immediacy.
Data was collected from 301 visitors through a mixed-methods survey combining closed-ended measures of emotional response with open-ended questions. The results show that visitors reported a broad range of emotions, most commonly positive or mixed, with a smaller proportion reporting negative responses. While most comments related directly to the exhibition content and personal wartime testimonies, some respondents explicitly connected their experience to the war in Ukraine, illustrating how contemporary crises can shape the interpretation of historical heritage.
The findings highlight that emotions function as interpretive lenses through which audiences make sense of difficult heritage, and that present-day events may reframe the meanings attached to the past. The article contributes to international discussions on heritage and memory by demonstrating how crisis contexts affect visitor experience, offering insights for museums engaging the public with contested histories during turbulent times